Implementation of Technology-Based Learning Objectives in Deep Learning by Islamic Education Teachers: The Perspective of the Vice Principal for Curriculum at State Senior High School 9 Pontianak - Syukri, M.; Wahab, Wahab (Program Magister Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2025)
This study aims to analyse the implementation of technology-based learning objectives in in-depth learning by Islamic Education teachers from the perspective of the Deputy Headmaster for Curriculum at State Senior High School 9 Pontianak. This study uses a qualitative approach with a case study method. Data were collected through in-depth interviews with the main informant, namely the Deputy Headmaster for Curriculum, referred to in this study as the Deputy Headmaster for Curriculum, and supported by observations of Islamic Education teachers. The data were then analysed using Miles and Huberman's method, which includes data reduction, data presentation, conclusion drawing and verification. The results of the study show that Islamic Education teachers have begun to utilise technology in the learning process, such as the use of Canva, Wayground (Quiziz) and YouTube. However, this implementation is still dominant in the aspect of material delivery and does not yet fully support the achievement of deep learning that integrates cognitive, affective and spiritual aspects. The deputy headmaster for curriculum assessed that the main supporting factors were the availability of digital infrastructure and adaptive school policies, while the inhibiting factors included the low digital literacy of some teachers and limited time in designing project-based learning.